2022
DOI: 10.1021/acs.jafc.2c06136
|View full text |Cite
|
Sign up to set email alerts
|

High Value-Added Application of Natural Plant Products in Crop Protection: Construction and Pesticidal Activities of Piperine-Type Ester Derivatives and Their Toxicology Study

Abstract: To discover new potential pesticide candidates, recently, structural modification of natural bioactive products has received much attention. In this work, a series of new piperine-type ester derivatives were regio-and stereoselectively synthesized based on a natural alkaloid piperine isolated from Piper nigrum. Their structures were characterized by IR, mp, 1 H NMR ( 13 C NMR), and high-resolution mass spectrometry (HRMS). Against Tetranychus cinnabarinus Boisduval (Acari: Tetranychidae), compounds 4e, 4f, 4u,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 37 publications
(68 reference statements)
1
17
0
Order By: Relevance
“…There were lots of white spots destroyed by T. urticae on the seedling leaves in the CK-treated group, whereas in the MT/OMT (3/7)-and MT/OMT (3/7)/CN-treated groups, almost no small white spots were on the seedling leaves. These findings were the same as our previous report [58]. Photographs of control effects of those complexes against T. urticae are shown in Figures S4-S6.…”
Section: Acaricidal Activitysupporting
confidence: 91%
See 1 more Smart Citation
“…There were lots of white spots destroyed by T. urticae on the seedling leaves in the CK-treated group, whereas in the MT/OMT (3/7)-and MT/OMT (3/7)/CN-treated groups, almost no small white spots were on the seedling leaves. These findings were the same as our previous report [58]. Photographs of control effects of those complexes against T. urticae are shown in Figures S4-S6.…”
Section: Acaricidal Activitysupporting
confidence: 91%
“…Then, Petri dishes were placed in a light incubator (temperature: 26 ± 1 • C; RH: 60-80%; photoperiod: light/dark = 14/10 h). Finally, the dead mites were collected at 24, 48 and 72 h after treatment by the complex for scanning electron microscope (SEM) analysis [56,58].…”
Section: Analysis Of Morphology Of Cuticles 241 Pretreatment Of Mitesmentioning
confidence: 99%
“…Notably, their acaricidal activities were more potent than those of 7-oxycarbonylandrographolide, cholesterol, and osthole ester/amide derivatives [ 38 , 41 , 45 , 46 ]. When compared with our previous results [ 48 ], it suggested that introduction of the CH 2 between the phenyl/4-Fphenyl/4-Clphenyl and the carbonyl groups was very important for the acaricidal activity. Later, to obtain good acaricidal agents, R as the different substituted benzyl should be considered.…”
Section: Resultsmentioning
confidence: 50%
“…Obviously, it suggested that introduction of the furan-2-ylcarbonyloxymethylene group at the C-2 position of compound 1 was very important for aphicidal activity against E. lanigerum . Based on our previous results [ 48 ], it demonstrated that introduction of the CH 2 between the (un)substituted phenyl and the carbonyl groups was not necessary for aphicidal activity against E. lanigerum .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation